The influences of city on income polarization in Malaysia - Yusoff, Noraniza (2018)
Urbanization and the advancement of the modern city currently are essential questions that city stakeholders have to overcome, particularly in the developing nations in Southeast Asia. The activity of suburbanization enhances urban challenges and faster the decrease of city centers, remains the centers with Tcw true sources, higher economic and social reliance and increasing public expense.The objective of the study is to determine the relationship among city and Income polarization. 'The research question is why city influence phenomena of income polarization?.Data collection phase undertook in the year 2016 utilized quantitative approach via survey by questionnaire entailed 434 respondents to obtain primary data for this basic study. Data analyses constitute of Spearman correlation, Ordinal regression and scatterplot. Results show that city effect and pred!ct the phenomena of income polarization. This cvnIirms that city as~ocistcdw ith income polarization.